Pain Patients and Who they Live with: A Correlational Study of Coresidence Patterns and Pain Interference - Jacob M Vigil; Patricia Pendleton; Patrick Coulombe; Kevin E Vowles; Joe Alcock; Bruce W Smith (Pain Research and Management)
BACKGROUND: Mixed associations have been observed between various aspects of ‘social support’ and patient pain experiences